Step 1

we have to find the eighth term of the arithmetic sequence whose first term is 4 and whose common difference is -7.

Step 2

Let the eighth term is denoted by \(\displaystyle{a}_{{{8}}}\)

here

\(\displaystyle{a}_{{{1}}}=\) first term \(\displaystyle={4}\)

\(\displaystyle{d}=-{7}\)

now as we know that \(\displaystyle{n}^{{{t}{h}}}\) term is given as

\(\displaystyle{a}_{{{n}}}={a}_{{{1}}}+{\left({n}-{1}\right)}{d}\)

where \(\displaystyle{a}_{{{1}}}\) is the first term an d is the common difference.

\(\displaystyle{a}_{{{8}}}={4}+{\left({8}-{1}\right)}{\left(-{7}\right)}\)

\(\displaystyle{a}_{{{8}}}={4}+{7}{\left(-{7}\right)}\)

\(\displaystyle{a}_{{{8}}}={4}-{49}\)

\(\displaystyle{a}_{{{8}}}=-{45}\)

we have to find the eighth term of the arithmetic sequence whose first term is 4 and whose common difference is -7.

Step 2

Let the eighth term is denoted by \(\displaystyle{a}_{{{8}}}\)

here

\(\displaystyle{a}_{{{1}}}=\) first term \(\displaystyle={4}\)

\(\displaystyle{d}=-{7}\)

now as we know that \(\displaystyle{n}^{{{t}{h}}}\) term is given as

\(\displaystyle{a}_{{{n}}}={a}_{{{1}}}+{\left({n}-{1}\right)}{d}\)

where \(\displaystyle{a}_{{{1}}}\) is the first term an d is the common difference.

\(\displaystyle{a}_{{{8}}}={4}+{\left({8}-{1}\right)}{\left(-{7}\right)}\)

\(\displaystyle{a}_{{{8}}}={4}+{7}{\left(-{7}\right)}\)

\(\displaystyle{a}_{{{8}}}={4}-{49}\)

\(\displaystyle{a}_{{{8}}}=-{45}\)